2020
DOI: 10.1242/dev.191726
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of the tear drainage system requires Prickle 1-driven polarized basement membrane (BM) deposition

Abstract: In terrestrial animals, the lacrimal drainage apparatus evolved to serve as conduits for tear flow; however, little is known about the ontogenesis of this system. Here, we defined the anatomy of the fully formed tear duct (TD) in mice, characterized crucial morphogenetic events for the development of tear duct components, and identified the site for primordial tear duct (PTD) initiation. We report that the PTD originates from the orbital lacrimal lamina (LL), a junction formed by the epithelia of the maxillary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…24 The seemingly paradox observations could be explained when considering that AB polarity and BM basal deposition form a positive feedback loop only after their establishment (Figure 7K secretion in multiple tissues. 21,23,24 Recently, we also found that Prickle1 expression in the VE is much stronger than the epiblast in early embryogenesis. Thus, a careful in vivo characterization of the BM defect using Prickle1 conditional knockout mice combined with VE or epiblast specific Cre lines will be needed in the future to clarify which germ layer dominates BM secretion.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…24 The seemingly paradox observations could be explained when considering that AB polarity and BM basal deposition form a positive feedback loop only after their establishment (Figure 7K secretion in multiple tissues. 21,23,24 Recently, we also found that Prickle1 expression in the VE is much stronger than the epiblast in early embryogenesis. Thus, a careful in vivo characterization of the BM defect using Prickle1 conditional knockout mice combined with VE or epiblast specific Cre lines will be needed in the future to clarify which germ layer dominates BM secretion.…”
Section: Discussionmentioning
confidence: 86%
“…Loss of Prickle1 altered cytoskeleton and vesicle compartments of the epiblast and the embryonic tear-duct epithelial cells. 23,24 Interestingly, it is the disruption of microtubules or vesicle trafficking but not actin assembly that completely abolished BM. In an effort to search for proteins responsi- Although the initial BM formation is largely independent of AB polarity, as revealed by this study, studies from other systems suggest that basal BM is required for the AB polarity, [9][10][11][12] and AB polarity is also crucial for BM basal deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Anatomically, the nasolacrimal duct, conjunctiva, and LG epithelia are continuous and share the same origin from the embryonic conjunctival ectoderm. 25 , 42 Functionally, the lymphoid tissues of the three parts of the tear apparatus are also connected, 43 and, as a result, the nasolacrimal system plays an important role in ocular surface innate immune defense. 44 Despite the intimate relationships of the three major components of the tear apparatus, the functional connection between either of the two has not been established.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Recently, we described the mouse TD ontogenesis and anatomy, demonstrating its similarity to humans using a Prickle1 mutant mouse line. 25 This is, to our knowledge, the first genetic model having incompletely developed TD (GTDOB) by disruption of Prickle1 gene. 26 28 …”
mentioning
confidence: 95%